Analisis Pengawasan Melekat Terhadap Disiplin Kerja Di Kantor Camat Ratu Samban Kota Bengkulu - Wulansari, Cici; Hakim, Kahar; Marianata, Anita (JIAP (Jurnal Ilmu Administrasi Publik), 2024)
The purpose of this study was to analyze the implementation of supervision related to employee work discipline at the Ratu Samban District Office, Bengkulu City. This study is classified as quantitative research using primary data in the form of numbers from questionnaires given to 19 employees at the Ratu Samban District Office, Bengkulu City. The method of findings includes data collection through observation, documentation, questionnaires, and literature studies. Quantitative data analysis using SPSS 20. The results of the study indicate that inherent supervision significantly influences the improvement of employee work discipline at the Ratu Samban District Office, with a contribution of inherent supervision of 35.3% to work discipline. This indicates that the more effective supervision that includes monitoring, inspection, and evaluation, the higher the level of employee discipline in carrying it out. This study enriches the literature on the relationship between inherent supervision and work discipline in the context of local government. By referring to the theory of managerial control and reinforcement, the results of this study underline the importance of the role of inherent supervision in creating disciplined behavior in the work environment. Good supervision can increase employee compliance with organizational rules and reinforce positive behavior.